Flexibility of exercise capacity during nestling feeding in blue tits - Engert, Elana Rae ; 0000-0002-6383-450X; Nord, Andreas ; 0000-0001-6170-689X; Andreasson, Fredrik; Nilsson, Jan-Åke (Journal of Experimental Biology, 2025)
Nestling feeding in altricial birds is a physiologically demanding phase of the annual cycle. Accordingly, parental effort in breeding songbirds has been suggested to be limited by the maximum capacity to perform sustained aerobic work. However, the maximum capacity for exercise and plasticity thereof is understudied in free-living, breeding songbirds. We tested two predictions related to the plasticity of exercise capacity in breeding blue tits with increasing workload due to an increasing demand for nestling feeding as nestlings grow older and with experimentally increased brood size. We measured the maximum exercise-induced metabolic rate and endurance of parents both early on and at the peak of nestling feeding, and found that exercise capacity increases with nestling age. Parents of enlarged broods had higher exercise capacity than those with unmanipulated broods, but this was only true for young birds. We suggest that the exercise capacity of breeding birds is a plastic trait and depends on the amount of exercise that has been performed in the preceding days. However, the potential for an increase in exercise capacity is likely to be affected by parental age and experience, behavior, resource availability, in addition to nestling age and brood size.